MENINGKATKAN MINAT SENI MUSIK PADA SISWA SEKOLAH DASAR - Syahra Ahta Pratiwi1; Dinda Andiana (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to examine strategies in increasing elementary school students' interest in learning music arts. Through a literature study approach, this study examines various relevant sources to gain an in-depth understanding of the factors that influence students' interest and effective learning methods. The results of the study indicate that the use of song-based teaching materials, simple musical instruments, learning by doing models, ensemble activities, and art performances such as musical dramas have been proven to be able to increase students' interest, motivation, and active participation. Creative and enjoyable music arts learning not only encourages students' emotional and social involvement, but also contributes to cognitive, affective, and psychomotor development. Therefore, the application of innovative learning strategies is very important to create meaningful learning experiences and support the development of students' artistic potential and character from an early age.